Decomposição de carvão com elevado teor de cinzas para determinação simultânea de As, Cd, Hg, Pb e S por ICP-OES - Corazza, Gabriela (2015)
In this work, sample preparation methods for decomposition of coal with high ash content (14- 54%) for further simultaneous determination of As, Cd, Hg, Pb and S by inductively coupled plasma optical emission spectrometry (ICP-OES) were evaluated. Coal samples were initially decomposed by dry ashing according to the reference method (ASTM D 6357-11). Lead and S losses were observed probably due to the high temperature during combustion and the use of an open system. Thus, the decompositions by microwave-assisted wet digestion (MAWD) was also evaluated. Decomposition were carried in closed vessels out with concentrated acids under different conditions: i) 8 mL HNO3, ii) 7 mL HNO3 + 1 mL HF and iii) 6 mL HNO3 + 2 mL HF. The use of HF was necessary due to the inorganic content, allowing the quantitative recovery for all analytes. Decomposition by microwave-induced combustion (MIC) was also optimized, in order to promote a complete analyte recovery once incomplete recovery was observed, mainly for As and Pb, due to the ash content of coals. Parameters related to the pressure for pellets preparation, the use of additives (microcrystalline cellulose and NH4Cl), the composition and concentration of absorbing solution (HNO3, HCl, HNO3 and HCl 2:1, HNO3 and HCl 1:1, and HNO3, HCl and H2O 1:1:1) and the reflux step of absorbing solution (5 or 15 min) were evaluated. Quantitative recoveries were obtained when 300 mg of NH4Cl were added to the samples and using HNO3 and HCl (2:1) as absorbing solution with 5 min of reflux step after combustion. In addition, a faster method, attending to the green chemistry concepts, was evaluated for coal decomposition by MIC and further S determination by ICP-OES. In this case, optimizations were carried out in order to decrease the decomposition time (reflux and cooling steps) and evaluate the better absorbing solution according to the detection technique available. Optimized MIC conditions for S analysis were 6 min of decomposition (1 min of irradiation + 5 min of waiting) with 2 mol L-1 HNO3 as absorbing solution. After optimizing MIC, coal samples A, B and C, with ash content of, 14, 32 and 54%, respectively, were decomposed by the three methods (ASTM D 6357-11, MAWD and MIC) and no statistical difference was observed for As and Cd (ANOVA) among all methods and for Hg, Pb and S (test t-Student) by MAWD and MIC. Accuracy for MAWD and MIC procedures was evaluated by the use of certified reference materials (CRMs) of coal (NIST 1632c, SARM 19 and SARM 20). No statistical difference (test t-Student) was observed for As, Cd, Hg, Pb and S, demonstrating the suitability of MIC as sample preparation method for coal with high ash content. The limits of detection (LDs) for MIC were always lower than MAWD and similar to those obtained by the official method (ASTM D 6357-11).